Systemic lupus erythematosus presenting as lupus erythematosus tumidus and lupus nephritis: a case report - Meriam Hajji; Imen Gorsane; Samaraa Badrouchi; Noureddine Litaiem; Soumaya Rammeh; Fethi Ben Hamida; Ezzeddine Abderrahim (Journal of Medical Case Reports, 2023)
Abstract Background Lupus nephritis and lupus erythematosus tumidus (LET) are uncommon manifestations of systemic lupus erythematosus (SLE), and their coexistence as the initial presentation of SLE is exceedingly rare. Here, we report such a case, emphasizing the diagnostic challenges and therapeutic implications of this unusual association. Case report A 38-year-old North African woman presented in Nephrology department with a history of lower extremity edema, fatigue, and weight loss of 3 kg in 4 weeks. Physical examination revealed LET lesions on the chest and the Neck. Laboratory investigations showed lymphopenia, low C3 and C4 complement levels, positive antinuclear antibodies, anti-dsDNA antibodies, and anti-SSA/Ro antibodies. Renal function tests showed normal serum creatinine and nephrotic proteinuria. Renal biopsy revealed Class V lupus nephritis. Skin biopsy confirmed the diagnosis of LET, with the presence of lymphohistiocytic infiltrates and dermal mucin. The patient was diagnosed with SLE based on the 2019 EULAR/ACR criteria and treated with prednisone (1 mg/kg/day) and hydroxychloroquine. She showed significant improvement in her cutaneous and renal symptoms at 6 and 12 months follow-up. Conclusion The rarity of the coexistence of LET and lupus nephritis as the initial manifestation of SLE, especially in the North African population, underscores the need for further research to elucidate the immunopathogenic mechanisms and prognostic factors associated with this association.